082 Efficacy and Safety of Hyaluronic Acid Filler Injection as Compared to Polylactic Acid Filler for Temporary Penile Augmentation: A Multi-Center, Patient/Evaluator-Blinded, Randomized Control Trial with a Safety Extension. (1st May 2022) - Ahn, ST; Cho, SB; Lee, HS; Han, DE; Lee, DH; Shim, JS; Kim, SW; Moon, DG
ABSTRACT: Introduction: Soft tissue augmentation using hyaluronic acid (HA) filler has grown rapidly in recent years, while clinical studies, especially randomized control trial, in penile augmentation (PA) using HA filler rarely conducted. Objective: T his study aimed to investigate the efficacy and safety of HA filler injection for temporary PA as compared to polylactic acid (PLA) filler. Methods: The present prospective, patient/evaluator-blinded, multi-center study randomized 74 patients with small penis syndrome, which defined as the anxiety felt when one's penis is being observed because of concern that the penis is small, to HA filler injection or PLA filler injection for PA. Penile girth and satisfaction, were assessed at baseline and at 4, 12, and 24 weeks after injection. Safety profile evaluation was extended for 48 weeks for HA filler injection group. Results: Grossly, both filler materials were evenly distributed, and led to a significant volume expansion for up to 24 weeks post-injection (Figure 1) In both group, mean penile girths significantly increased at 4 weeks post-injection (2.7±1.0 and 2.3±1.1 cm mean increases in the HA and PLA groups, respectively; each p<0.001). Although, both filler gradually decreased, penile girth increases adequately lasted for 24 weeks (2.3±1.3 and 2.0±0.9 cm mean increases from baseline in the HA and PLA groups, respectively; each p<0.001). (Figure 2) Satisfactions for penile appearance and sexual life were significantly increased at 24 week in both group. Adverse event related to filler injection were reported in 2 (5.56%) and 3 (7.89%) patients in HA and PLA groups, respectively during 24 weeks. And 1 case was recorded after extensions for 48weeks for HA group. Conclusion: HA filler was similarly effective with PLA filler for temporary PA in men with small-penis syndrome and can be used safely for a long time until 48 weeks.